ADAPTOGENIC ACTIVE COMPONENT FROM MYXOPYRUM SMILACIFOLIUM - Siju, E. N.; Samu, Jolly; Minil, M.; Rajalakshmi, G. R. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The present study was designed to investigate the adaptogenic active component from the extracts of Myxopyrum smilacifolium. Methods: The plant extract was undergone different separation technique viz precloumn, HPTLC, etc for isolation of pure compound. Thereafter the pure compound was subjected to IR, NMR, LC-MS for structural elucidation. Results: Chemical characterization of the adaptogenic fraction by spectroscopy showed iridoid glycoside as major constituents. Conclusion: The present study showed iridoid glycoside is considered the adaptogenic agents of Myxopyrum smilacifolium Blume.